2019
DOI: 10.1159/000503333
|View full text |Cite
|
Sign up to set email alerts
|

Dental Health Status and Oral Health Care in Nursery School-Aged Children and their Parents Living in Poznan (Poland)

Abstract: Objectives: The aim of this study was to evaluate the dental health status of nursery age children and parents. The use of dental services was assessed. Subjects and Methods: The study was performed in nursery schools located in Poznan, Western Poland. Clinical examination was carried out in 157 children (48.41% males and 51.59% females), aged 10–42 months. Dental health status (the number of teeth with caries, fillings and extracted) of their parents was determined on the basis of data obtained from a questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Dental caries (decay) is a multifactorial chronic disease that poses a very serious global health problem since it involves most of the population [ 1 , 2 , 3 ]. Numerous environmental and individual risk factors are responsible for this disorder’s occurrence and development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dental caries (decay) is a multifactorial chronic disease that poses a very serious global health problem since it involves most of the population [ 1 , 2 , 3 ]. Numerous environmental and individual risk factors are responsible for this disorder’s occurrence and development.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous environmental and individual risk factors are responsible for this disorder’s occurrence and development. These components are related e.g., to the genetic factors, the transmission of germs between hosts, bacterial flora, flow rate and composition of saliva, hygienic and dietary habits, socioeconomic status, parental education, and oral health care availability [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier in this article we cited selected recommendations which should be communicated to parents and caregivers since their leading role as promoters of healthy behaviours in their children has been demonstrated in numerous studies [ 10 ]. It was suggested that healthcare professionals should educate parents on the importance of regular dental visits and home-based prevention to eliminate or reduce the influence of ECC risk factors and strengthen the protective ones [ 10 , 15 , 36 ]. Moreover, it was proposed that fluoride toothpaste manufacturers, public health institutions, and national societies should provide the public with clear oral hygiene visual instructions on toothpaste packaging and in toothbrushing manuals [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results confirmed similar earlier findings [ 10 ]. Other authors reported that frequent dental visits of the parent resulted in an almost 4-fold increase of the chances of similar practices in the child, while both parents visiting a dentist regularly were associated with an increased number of caries-free children [ 30 , 36 ]. The child’s chances of being caries-free were greater when parents self-assessed their oral health as good, whereas caries in child’s primary dentition was associated with parents’ oral health [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The complex association of parents' oral health knowledge, attitudes, and behaviors with children's oral health behavior and dental caries has been investigated to improve children's oral health. [3,13,14] Researchers have identified numerous factors associated with dental caries. [14] However, their direct or indirect effects on oral health outcomes remain unclear.…”
Section: Discussmentioning
confidence: 99%